Future of the forest : struggles over land and law in India - Vaidya, Anand P., 1982- (Ithaca : Cornell University Press, 2025)
"Future of the Forest is a historical and ethnographic account of the life of India's 2006 Forest Rights Act. The book follows the law from the movements that pushed for its passage to a North Indian forest village, showing how the law's meaning was shaped through ongoing collective action"--
How the forests became Indian -- Historical injustices and the movement to create the Forest Rights Act -- The Law as rumor -- Abandoned solidarities and new legal futures -- National politics and the scales of the Forest Rights Act.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
JSTOR
Keywords: India; Forestry -- Law and legislation -- India; Forest management -- India; Forest people -- Legal status, laws, etc. -- India; Forests and forestry -- Social aspects -- India; Forêts -- Gestion -- Inde; Forêts -- Aspect social -- Inde; POLITICAL SCIENCE / Human Rights; Electronic books